Reflexão sobre ética empresarial no contexto de um jogo de empresas: um estudo sobre possibilidades pedagógicas e técnicas - Bonocielli Jr, Sergio Gilberto (2009)
Recent scandals seen in the Brazilian and international scenes, involving some form of violation of ethical principles by the managing boards of companies, have shown the need to reinforce teaching, training and reflection about Business Ethics, both in the corporate and in the academic worlds. A very complex subject, the teaching of Business Ethics to Business students has been the focus of several studies. Indirect methods, such as case studies and simulations, are among the various possible forms of allowing students adequate reflection on Ethics. However, business games, understood as a simulation of business reality, have been scarcely used to this end. Applying mixed methods techniques, which allow multiple forms of data gathering, this paper presents an analysis of the technical and pedagogical viability of inserting the reflection about Business Ethics in the context of an existing business game. Through the results obtained during the application of the business game in a Brazilian university, it shows how it is possible to use this tool, as a means for both teaching and reflecting on Business Ethics. As an example of the uses of business games as a research laboratory, this paper describes how participating students behaved when confronted with ethical dilemmas during the business game and how they based their decisions.